N,N,N-Triphenylselenylisocyanuric Acid (TPSCA): A New Versatile Reagent for α-Phenylselenenylation of Aldehydes and Ketones - Movassagh, Barahman; Takallou, Ahmad (Synlett, 2015)
A new, versatile reagent, N,N,N-triphenylselenyl-isocyanuric acid (TPSCA) has been prepared, characterized, and used as a source of the electrophilic phenylselenyl group. This relatively stable compound was utilized for an efficient α-selenenylation reaction of aldehydes and ketones catalyzed by l-prolinamide under mild reaction conditions. The organocatalytic asymmetric α-selenenylation of an aldehyde was also studied and the reaction was found to proceed with high enantioselectivity (96% ee).
Keywords: electrophilic selenenylation; isocyanuric acid; aldehydes; ketones; prolinamide